Jalan Damai Sufi Nusantara : Gagasan Dan Karya Wali Songo, Hamzah Fansuri, & Syamsuddin As-Sumatrani Bagi Perdamaian - Boydo Rajiv Hutagalung (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2020)
This article discusses on how the thoughts or dakwah’s methods of some Islam figures in the past, which we can call them as Nusantara’s Sufis. According to the writer’s perspective, the dakwah’s methods of Nusantara’s Sufis contributes positively for harmony, tolerance, and peace. Some of them are: The Wali Songo, Hamzah Fansuri, and Syamsuddin As-Sumatrani. Their thought and and their spirituality can be categorized as Social Tasawuf which is not only oriented in verticalistic spirituality but also to bring harmony, peace, and acceptance to culture.